Temperature based fan speed control - Zaieni, Muhammad Amir Akmal; Wan Saiful Bahari, Syed Abdul Rahman (2016)
Table fan are one of the most commonly used equipment in the Malaysia. The innovation and the improvement of the table fan in term of the power consumption of electricity will give a huge impact on the table fan market value. Almost every household in Malaysia have a table fan, this shows how much Malaysian need fan in this region. Malaysia’s climates are hot and humid all year around. Therefore, table fan plays a huge role on cooling down the citizens in their house. Though the table fan marketing in Malaysia is good, the problem arose when people tend to forget or intentionally let the table fan turn on when they do not use it or when the temperature is decreasing. Some, Malaysian also use fan when the weather is not really hot and some use the fan table even when they turn on the air conditioner. With the help of technological advancement, these problems can be tackled head on with the use of a temperature sensor. The sensor will detect the surrounding temperature and a microcontroller will be used as a brain which will receive the temperature from the sensor and will gives out a suitable command to the table fan according to the surrounding temperature.